Determinants of QRIS as a Payment Method for ZIS at BAZNAS Banjarmasin: The Role of Perception, Ease of Use, and Religiosity - Maulina, Denissa Salsabila; Mubarak, Zaki; Hidayat, Muhammad Rifqi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The rapid development of technology has driven the adoption of digital payment systems, one of which is QRIS (Quick Response Code Indonesian Standard), which facilitates transactions. This study aims to analyze the effect of perceived benefits and ease of use on the decision to use QRIS at BAZNAS Kota Banjarmasin, with religiosity as a moderating variable. The research method used is a quantitative approach with data collected through questionnaires and analyzed using PLS (Partial Least Squares) with SmartPLS software. The population of the study consists of the people of Kota Banjarmasin, with 100 respondents. The results show that perceived benefits and ease of use positively influence QRIS adoption. Religiosity does not strengthen the effect of perceived benefits, but it can strengthen the effect of ease of use on the decision to adopt QRIS.